The Effect of Autogenic Relaxation and Positive Affirmations on Anxiety Levels and Vital Signs of Patients - Basri, Ahmad Hasan; Indawati, Lilis Tri; Revita, Natalia Christin Tiara (Universitas Muhammadiyah Lamongan, 2025)
Introduction: Anxiety is a word used to describe feelings of uneasiness, worry, and at the same time fear so that anxiety can affect the TTV of someone who does the examination. this study aims to determine the description of anxiety levels and TTV in patients. This anxiety needs attention and nursing intervention because the patient's emotional state will affect body function, especially in changes in Vital Sign, which can affect the results of Medical Check Up (MCU) which is less accurate and does not match the actual condition experienced by the patient. Methods: This research design is descriptive research. Has a single variable, namely anxiety level and TTV. The population of this study was 100 with purposive sampling technique that met the inclusion criteria so that it became 80 respondents. Carried out on November 1 to November 23, 2024. Data were collected using anxiety levels and vital signs using a questionnaire instrument. Data analysis using the Wilcoxon statistical test to determine the level of significance α < 0.05, if p < 0.05 then there is an effect of Autogenic Relaxation and Positive Affirmation on the level of anxiety and vital signs of patients. Results: Most respondents had mild anxiety 54 patients (67.5%) after the intervention and almost all respondents had abnormal TTV 63 patients (78.8%) after the intervention.In this study with the willcoxon test, there is an effect of the combination of autogenic relaxation (p-value = 0.000), and positive affirmations (p-value = 0.000) on anxiety levels. Conclusion: The MCU clinic provides audio about providing autogenic relaxation and positive affirmations in the waiting room to reduce patient anxiety so that patients have accurate medical examination results. Keywords: Anxiety; Blood Pressure; Patients